Meningkatkan Daya Saing UMKM dengan Strategi Digital Marketing - Rumyeni, Rumyeni; Angela, Sesdia; Mustaqimmah, Nurul; Bagasari, Lintang Arum; Rimayanti, Nita (MENARA RIAU, 2025)
The rapid growth of digitalization has made digital marketing crucial for Micro, Small, and Medium Enterprises (MSMEs). However, many MSMEs in Siak Regency have not fully utilized digital marketing strategies, limiting their market competitiveness. This community service aims to enhance digital marketing skills among MSMEs through training and mentoring. The method used is a participatory approach, providing training on digital literacy, social media usage, and e-commerce platforms. Continuous mentoring ensures that participants can apply the strategies learned to their business activities. The results of this community service show a significant improvement in digital marketing skills among participants, contributing to increased sales and market reach of MSMEs. Additionally, active participation in training and support from academics fostered a more adaptable business ecosystem towards technological changes. Thus, this program successfully helped MSMEs in Siak Regency become more competitive in both local and national markets.